PTU-004 Incidental findings in the UK Bowel Cancer Screening Programme. (23rd September 2015) - Chakrabarty, G; Sadler, G; Bouwer, M; Pollok, R; Groves, C; Forton, D; Leicester, R; Poullis, A
Abstract : Introduction: The UK National Bowel Cancer Screening (BCS) Programme aims to identify individuals between the ages of 60 and 70 years at risk for bowel cancer. Those with a positive faecal occult blood test (FOBT) are offered screening colonoscopy. We aimed to quantify and characterise the incidental findings in individuals attending for colonoscopy. Methods: We audited the St George's Hospital BCS database from Nov 2006 to Sep 2009. We determined the various incidental findings and symptoms in this cohort. Case notes of patients under local follow-up were reviewed. Results: 1286 patients have been screened (744 male, 542 female). Colorectal cancer was diagnosed in 128 cases (9.95%). 61 patients had findings other than colonic adenoma or colorectal cancer. 31 individuals (50.8%) were found to have inflammatory bowel disease (IBD) (21 Male, 10 Female). Out of them nine had ulcerative colitis (29%), 11 Crohn's disease (35.4%) and in 11 cases IBD was of indeterminate subtype (35.4%). Colitis was a pre-existing diagnosis in eight (25.8%) patients, none of who were receiving treatment at the time of colonoscopy. 11 cases of radiation proctitis and one radiation enterocolitis was found (19.6%). All radiation proctitis was due to radiotherapy for prostate cancer and the enterocolitis due to radiotherapy for lymphoma. We identified three cases of neuroendocrine tumours (4.9%) and one granular cell tumour. Three neuroendocrine tumours were found in the rectum and the granular cell tumour in the caecum. We found seven cases of angiodysplasia (11.5%), and their distribution was 2 in rectum, 2 in caecum, 2 in right colon and 1 in transverse colon. Other incidental findings were: 3 solitary rectal ulcer syndrome, 1 Peutz-Jeghers syndrome, 1 threadworm infection, 1 lipoma and 1 case of lymphoid polyp. None of the cases had coexisting colorectal cancer. Conclusion: The relative risk of having IBD in the BCS cohort is approximately nine times greater than in the background population. The majority of IBD patients seemingly had not been investigated previously. These findings suggest that a small but significant group of patients with IBD remain undiagnosed into the seventh decade of life. Radiation colitis and angiodysplasia are also significant cause of positive FOBT. The risk of neuroendocrine tumour (0.23%) in the BCS cohort is hundred times more than the background population. Our findings suggest there has been, prior to the BCS programme, a significant proportion of Colonic tumours other than colorectal cancer that were not identified.